HUBUNGAN ANTARA KEGIATAN MEMBANGKITKAN MOTIVASI KERJA OLEH KEPALA SEKOLAH DENGAN KINERJA GURU SEBAGAI MANAJER KELAS - Sujono Surokarijo (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2006)
The objective of this research is to know the relationship between principals’ activities to increase the working motivation based on teachers’ evaluation and the teachers’ performance as classroom managers. This research is conducted in Government Primary Schools, Kediri Municipality, East Java Province. The method employed in this research is survey covering 104 classroom teachers as samples, which are selected by cluster random sampling technique. Data are collected by using questionnaires and are analyzed by using simple correlating technique and linear regression technique. The result shows, there is a positive relationship between principals activities to increase the working motivation based on teachers evaluation and the teachers performance as classroom managers. It can be concluded that the more active principals to increase the working motivation is improved the teachers performance.